The chronology of ancient nations : an English version of the Arabic text of the Athar-ul-Bakiya of Albiruni or vestiges of the past - el-Biruni, Ebü’r-Reyhan Muhammed bin Ahmed, 973-1061 (Frankfurt am Main)
xvi, 464 s.